African Futures Past: Material Horizons of Peasant Expectations in Senegal - Richard, François (Journal of Contemporary Archaeology, 2019)
Recent anthropological research in Africa has been buzzing with the question of “futures”. In times of economic uncertainty and global volatility, in areas of the world struck by widening inequalities, poverty and risk, where people have been compelled to try their luck abroad, the future is a pressing concern. It is also a key ethnographic prism for seeing how Africans (re)imagine time, expectations and possibility in late modernity. As recently pointed out by Janet Roitman, these conversations have acquired salience in relation to a global mood of “crisis”. Crisis, Roitman argues, does not mark an objective break with a normative “before”, a new experiential condition; rather, it is a narrative that imparts new moral weight to history in the present, and thus places a distinct spin on what and how futures can be imagined. Moved by this landscape of concerns, this article wonders what archaeology might contribute to contemporary feelings about “the future” in Africa. How does a look back, and a look forward from the past, help us to tease apart the temporalities that have shaped African worlds in the long term? How might a look at the kinds of time nested in material culture recast ongoing reflections on the present and future in Africa? How might it reframe the terms – crisis, melancholia, nostalgia, hope – in which continental futures are envisioned today? I hope to address these questions by reviewing recent archaeological research in rural West Africa and drawing on my own study of the hopes and anxieties that have framed peasant social expectations in Senegal over the past 300 years. My argument, though preliminary, is that examining Africa’s future pasts – material experiences and expectations of time in recent history – offers a lively contestation of the temporal frameworks into which the continent and its futures have been written.